2017
DOI: 10.1021/acs.est.7b04893
|View full text |Cite
|
Sign up to set email alerts
|

Carbon, Nitrogen, and Mercury Isotope Evidence for the Biogeochemical History of Mercury in Hawaiian Marine Bottomfish

Abstract: The complex biogeochemical cycle of Hg makes identifying primary sources of fish tissue Hg problematic. To identify sources and provide insight into this cycle, we combined carbon (δC), nitrogen amino acid (δN), and Hg isotope (ΔHg, ΔHg, δHg) data for six species of Hawaiian marine bottomfish. Results from these isotopic systems identified individuals within species that likely fed from separate food webs. Terrestrial freshwater inputs to coastal sediments were identified as the primary source of tissue Hg in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 56 publications
8
33
3
1
Order By: Relevance
“…The overall ∆ 199 Hg/∆ 201 Hg slope for penguin blood samples (1.16 ± 0.05) (Supplementary Fig. S2 ) is consistent with those previously reported in marine fish muscle 41 , 42 , 55 and seabird eggs 43 . Due to the predominance of MeHg in penguin blood, and assuming a potential diminution in MIF slope due to low DOC concentrations in subantarctic waters, the obtained ratio indicates an accumulation of residual MeHg that has principally undergone photochemical demethylation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The overall ∆ 199 Hg/∆ 201 Hg slope for penguin blood samples (1.16 ± 0.05) (Supplementary Fig. S2 ) is consistent with those previously reported in marine fish muscle 41 , 42 , 55 and seabird eggs 43 . Due to the predominance of MeHg in penguin blood, and assuming a potential diminution in MIF slope due to low DOC concentrations in subantarctic waters, the obtained ratio indicates an accumulation of residual MeHg that has principally undergone photochemical demethylation.…”
Section: Discussionsupporting
confidence: 90%
“…Theoretical slopes have been experimentally designed in aquatic systems 34 , corresponding to 1.36 ± 0.02 for MeHg photodemethylation and 1.00 ± 0.02 for inorganic Hg photoreduction in freshwater with natural DOC. Although studies in freshwater fish also reported Δ 199 Hg/Δ 201 Hg slopes close to 1.3 48 , 49 , 51 , slightly lower Δ 199 Hg/Δ 201 Hg slopes have been observed in marine organisms 41 43 , 52 55 . This effect may be the result of different ligands associated with Hg in aqueous solutions, such as dissolved organic matter 34 , 56 , 57 , or dissolved cations or halogens in seawater 40 .…”
Section: Discussionmentioning
confidence: 87%
“…For Station ALOHA the Δ 199 Hg/Δ 201 Hg ratio (Figure 4a) for all samples measured, with the exception of precipitation, was 1.21 ± 0.003 (York Regression,1 SD). This slope from the NPSG samples is similar to other marine and estuary fish studies (1.23 ± 0.01, 1 SD; Gehrke et al, 2011;Kwon et al, 2015;Li et al, 2016;Sackett et al, 2017;Senn et al, 2010) suggesting that the MIF values were produced by similar MMHg photochemical degradation mechanisms. This is supported by the good correlation between Δ 199 Hg and δ 202 Hg with a slope of 2.68 ± 0.12 (Figure 4b, 1 SD), which agrees with the experimentally derived photochemical degradation slope for MMHg of 2.43 ± 0.10 .…”
Section: Photochemical Demethylation Within the Mixed Layersupporting
confidence: 87%
“…Recently, Hg isotopic signatures have been used to characterize the complex biogeochemical cycle of this contaminant. Hg isotopes allowed to identify primary food sources of the accumulated-Hg in marine fish (Sackett et al, 2017(Sackett et al, , 2015 and to determine the habitats leading to Hg exposure, by discriminating between estuarine and oceanic affinities (Li et al, 2016, Senn et al, 2010 or benthic versus pelagic habits (Gehrke et al, 2011). These innovative analytical techniques, as well as the carbon stable isotope analysis of methylmercury (Masbou et al, 2015), are thus promising tools to get better insights in the origin, fate and ecodynamics of mercury in the marine food webs of this region with high fishing potential.…”
Section: E P T E D M a N U S C R I P T Conclusionmentioning
confidence: 99%